Why do people post when they or others are under risk or threat? Sociological and psychological reasons - Yaman, Fatih (Frontiers in Psychology, 2023)
Advances in technology make it easier for users to post content on social media. People can post different types of content in digital environments. Sometimes, they post such content in risky situations. Accordingly, this study aims to determine the sociological and psychological reasons why people record dangerous occurrences where they or other people are under risk or threat and post these recordings on social media. Within this general framework, this study aimed to answer five research questions. a) Why do individuals use social media? b) Why do people post on social media? c) What types of posts do people share on social media? d) What are the possible psychological reasons that push people to share such occurrences on social media? e) Why do individuals feel the need to record and share dangerous occurrences while under risk or danger? This study was conducted on the basis of a case study design, and interviews were conducted with two psychiatrists, two specialist clinical psychologists, and two sociologists. After the interviews, the reasons why individuals use social media platforms and post on the said platforms were laid out. It can be argued that the most prominent reason behind individuals' tendency to post while under risk or threat is isolation and inability to help.